POLG Gene Variants in Cervical Cancer Patients and Their Associations with Clinical and Pathomorphological Tumor Characteristics - Golubickaite, Ieva (J Clin Med, 2021)
Cervical cancer is one of the most common cancers in women worldwide. Human papillomaviruses are known to be the main, but not the only risk factor, of this cancer type. Despite all the knowledge on this cancer type, it is still a challenge to predict the course of the disease, and therefore, minimally invasive biomarkers are needed. This study aimed to analyze single-nucleotide variants in the POLG gene and assess the associations with tumor phenotype and patient outcome. A total of 172 cervical cancer patients were included in this study. Clinical and tumor data were gathered from medical records retrospectively. Single nucleotide variations were determined using TaqMan probes with Real-Time PCR. Significant associations between POLG rs3087374 and cervical cancer patients’ tumor histological type, stage, and tumor size were determined. The CA genotype and A allele of rs3087374 increased the probability of adenocarcinoma histological tumor type, IIIA stage, and T3 tumor size compared to CC genotype and C allele, respectively. Furthermore, patients with AA genotype in rs2072267 had longer metastasis-free survival than those with the GG genotype. Our data suggest that mitochondrial polymerase gamma encoded by nuclear POLG gene is important for specific tumor phenotype formation and patient outcome in cervical cancer.